Assessing the ecological status of Mediterranean coastal lagoons using macroinvertebrates. Comparison of the most commonly used methods - REIZOPOULOU, S.; SIMBOURA, N.; SIGALA, K.; BARBONE, E.; ALEFFI, F.; KAISAKIS, G.; ROSATI, I.; BASSET, A.; NICOLAIDOU, A. (Mediterranean Marine Science, 2014)
<!–[if gte mso 9]> Normal 0 false false false EL X-NONE X-NONE <![endif]–>Benthic communities were studied twice (autumn and spring) in three Mediterranean coastal lagoons located in Greece (Logarou) and Italy (Cesine and Grado-Marano). The species composition and distribution, the community diversity, the species richness, the dominant taxa and their ecological identity, the benthic trophic and biomass size structure were investigated in these lagoons and the the results were correlated with environmental variables.The overall similarity based on species composition and abundance among lagoons was low due to differences in dominant environmental factors, whereas variations of community diversity and species richness were mainly related to the degree of marine influence, reflecting the natural structure. The benthic classification indices AMBI, M-AMBI, BENTIX, BO2A, ISD and ISS were applied to assess the ecological status of the lagoons studied. Results showed that the biotic indices AMBI, M-AMBI, BENTIX, and BO2A are not adequately efficient due to the natural dominance of tolerant and opportunistic species and the correlation of species diversity to natural stress. ISD and ISS on the other hand, based on size distribution frequencies and on size spectra sensitivity respectively, had a good discrimination power between impacted and unimpacted sites. Results indicate that alternatively to the species sensitivity, other traits of the communities as the biomass or size structure could be more robust, sensitive and effective in assessing the ecological quality in lagoons. <!–[if gte mso 9]> <![endif]–><!–[if !mso]> <mce:style><! st1\:*behavior:url(#ieooui) –> <!–[endif] –><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Κανονικός πίνακας"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; –> <!–[endif] –>